Preparation And Characterization Of Cnt/Epoxy Nanocomposites Using Colloidal Polymerization Method - Faizul Hilma, Muhamad Nabil (Universiti Sains Malaysia, 2018)
Multiwalled Carbon Nanotube (MWCNTs) have an excellent properties to be used as a reinforcement material. However, due to its own nature behaviour, it tend to agglomerate in epoxy and this reduces the properties of nanocomposites. Oxidation by Hummers method is to overcome the agglomeration, but oxidized MWCNTs tend to re-agglomerate in epoxy. MWCNTs/epoxy nanocomposite sample have been prepared using colloidal polymerization method to overcome the re-agglomeration problem. The oMWCNTs have been mixed first with the low viscosity of TMD hardener. Field emission electron microscope (FESEM) proved that the oxidation reduce the entanglement of MWCNTs in order to produce better dispersion. HRTEM shows presence of damage at the surface of MWCNTs after oxidation. The reduction of crystallinity due to oxidation proved through XRD. Meanwhile, Raman spectroscopyshows the increase of defect through the D-band after oxidation. The presence of carboxyl functional group on the surface of MWCNTs after oxidation have been proved by FTIR. The oMWCNTs/epoxy nanocomposites prepared by colloidal polymerization method recorded the highest value for tensile strength. Apart from that, it also have the highest value for the thermal conductivity and also for dielectric constant.